2017
DOI: 10.1007/s12288-017-0895-8
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Rivaroxaban and Dalteparin in the Treatment of Cancer Associated Venous Thrombosis

Abstract: Venous thromboembolism (VTE) is a complication of malignancy that is associated with significant mortality. The CLOT trial showed superiority of dalteparin in comparison to warfarin in preventing VTE recurrence. Rivaroxaban has been approved for treatment of deep venous thrombosis (DVT) and pulmonary embolism (PE). In the absence of large randomized trials in the oncology population, the efficacy and safety of rivaroxaban for the treatment of VTE in cancer patients needs to be assessed. A single-center retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
(15 reference statements)
2
13
0
Order By: Relevance
“…On analyzing our data we found out that 50.6% of our population indication for anticoagulation was PE while it was only 29.7% in Chaudhury et al and 39% in Young et al; explaining that our patient population was more at risk at baseline. 17 We also noted that our study had larger percentage of gastric (7.3% Vs 3%) and cervical cancer (6.6% Vs 3%); which studies have shown to also cause a higher rate of VTE recurrence. 18 We also separately analyzed the demographic details of each one of the 6 recurrent DVT patients in rivaroxaban arm and found that 4 of 6 had gastric or pancreatic cancer, low albumin, BMI less than 22 and shared co-morbid (Diabetes, Hypertension and Coronary Artery Disease).…”
Section: Discussionsupporting
confidence: 50%
“…On analyzing our data we found out that 50.6% of our population indication for anticoagulation was PE while it was only 29.7% in Chaudhury et al and 39% in Young et al; explaining that our patient population was more at risk at baseline. 17 We also noted that our study had larger percentage of gastric (7.3% Vs 3%) and cervical cancer (6.6% Vs 3%); which studies have shown to also cause a higher rate of VTE recurrence. 18 We also separately analyzed the demographic details of each one of the 6 recurrent DVT patients in rivaroxaban arm and found that 4 of 6 had gastric or pancreatic cancer, low albumin, BMI less than 22 and shared co-morbid (Diabetes, Hypertension and Coronary Artery Disease).…”
Section: Discussionsupporting
confidence: 50%
“…explaining that our patient population was more at risk at baseline. 17 We also noted that our study had larger percentage of gastric (7.3% Vs 3%) and cervical cancer (6.6% Vs 3%); which studies have shown to also cause a higher rate of VTE recurrence. 18 We also separately analyzed the demographic details of each one of the 6 recurrent DVT patients in rivaroxaban arm and found that 4 of 6 had gastric or pancreatic cancer, low albumin, BMI less than 22 and shared co-morbid (Diabetes, Hypertension and Coronary Artery Disease).…”
Section: Discussionsupporting
confidence: 50%
“…It was noted that while recurrent VTE estimate in enoxaparin arm was comparable with previous RCTs (HOKUSAI-VTE, HOKUSAI-VTE CANCER and SELECT D); there was higher recurrent VTE estimate in rivaroxaban arm when compared to current data. On analyzing our data we found out that 50.6% of our population indication for anticoagulation was PE while it was only 29.7% in Chaudhury et al and 39% in Young et al; explaining that our patient population was more at risk at baseline [16]. We also noted that our study had larger percentage of gastric (7.3% Vs 3%) and cervical cancer (6.6% Vs 3%); which studies have shown to also cause a higher rate of VTE recurrence [17].…”
Section: Discussionmentioning
confidence: 60%